A spatial dialogue of heritage village between Kauman in Semarang and Seochon in Seoul toward preservation development - Suprapti, Atiek; Kim, Saehoon; Pandelaki, Edward E.; Firmandhani, Satriya W. (Journal of Architecture and Urbanism, 2018)
Semarang is one of big cities in Indonesia contains of multy ethnics. They traditionally settled down inside a group of villages. Kauman is the cultural heritage of Muslim settlement in Semarang. The peculiarity of local Muslims in Java’s coastline and the strong social cohesion colour the people’s daily life. Seochon in Seoul is a historic area and is the home for more than 670 hanoks. In 2008, Seoul Metropolitan Government issued a conservation plan and recruited a team of architects and academics to observe and investigate Seochon’s condition and discover the possibilities of conservation there. It turned out that Seochon has a great potential for revitalization. Nowadays, Seochon has become a tourism destination having both traditional and contemporary cultural value. This research aims to understand the efforts of preservation done by the government and public participation for the sake of preservation. This research used primary and secondary data and comparative study methods. Seochon village has been successful in developing preservation and preservation placed as the best example. The result of research showed that the conservation and preservation of Kauman needs a workable rules to manage and investigate the potential and resources. The result of this research could be used to any other cases similar to Kauman.